Implementasi Toleransi Antar Umat Beragama Sebagai Relevansi Dari Penerapan Moderasi Beragama - Mof, Yahya (el Buhuth: Borneo Journal of Islamic Studies, 2020)
This research aims to (1) describe the many different religious families in South Kalimantan, (2) describe the application of the value of tolerance in family communities of different religions, and (3) describe the implementation of wasathiyah Islam which is believed to avoid disputes and conflicts in family communities. different religion. This research reveals the implementation of religious moderation values in interfaith families with the research object focusing on the value of tolerance. The method used is a method to obtain as much information as possible using direct observation instruments, in-depth interviews and documentation. Direct observation is an effort to see directly the environment of religious moderation that exists in each family. The results of this research are concluded as follows: 1) Strengthening the value of religious moderation requires implementing an attitude of tolerance between religious communities wherever they are. 2) Indicators of religious tolerance among people in South Kalimantan are visible when Muslim family members want to go to the mosque, when fasting in the month of Ramadan, and Eid al-Fitr. 3) The application of wasathiyah Islam in the form of moderation is very necessary and recognized by all parties. 4) It is believed that the intensity of the implementation of wasathiyah Islam can avoid endless disputes and conflicts.